Dari Rapat Darurat Ke Putusan Final: Legasi Sengketa Pilkades Temanggung - Azzahra Pramesty Ramadhani; Muhamad Gibral Fetriko; Muhammad Rizqullah Mumtaz Akbar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the legality of the State Administrative Decision (KTUN) issued by the Regent of Temanggung No. 141677/2013 ratifying the Purwosari Village Head Election (Pilkades) results in Temanggung Regency, challenged via Semarang Administrative Court (PTUN) Decision No. 004G/2014/PTUN.SMG. The core research questions address: (1) whether the parties' positions and the KTUN meet formal requirements under PTUN procedural law, and (2) the judges' rationale regarding the vote recount mechanism absent explicit regulation in Temanggung's Regional Regulation (Perda) No. 5/2007 and Regent Regulation (Perbup) No. 6/2007 from the perspective of General Principles of Good Governance (AUPB). Employing a normative juridical approach, this research draws on primary legal materials including statutes (UU PTUN No. 51/2009, Perda Temanggung No. 5/2007, Perbup Temanggung No. 6/2007) and court decisions, alongside secondary sources such as journals and legal literature; data collection relies on library studies, with analysis via statutory, conceptual, and case study methods using qualitative descriptive techniques. Findings reveal that the KTUN satisfies formal elements and attributive authority, while the court rejected the claim, deeming the recount aligned with AUPB, committee-witness consensus, and legal certainty objectives. The study's novelty lies in proposing targeted regulations for Pilkades vote reconstruction protocols, enriching discourse on preventing recurrent village-level administrative disputes in Indonesia.